Organic Agriculture in Least Developed Countries in Relation to the Development of the Organic Farming Sector in Poland. The Example of African Countries versus the Organic Sector in Poland - Rydz‑Żbikowska, Anna (Comparative Economic Research. Central and Eastern Europe, 2020)
Over the past few years, organic farming has seen a dynamic development globally. In 2015, the global market for organic products was €81.6 billion, rising to more than €90 billion in 2018 (Światowy rynek produktów ekologicznych osiągnął wartość 90 mld euro 2019). There has also been a significant rise in the production of organic products by the group of Least Developed countries (LDCs) (such as African countries), which are being supported by all the World Trade Organisation negotiations within the Doha Round. The aim of this article is to present different definitions of organic farming according to the most important international organizations. Furthermore, it will examine the status of the organic farming sector in selected examples of Africa’s LDCs and investigate the results of Doha’s negotiations within the agricultural market (particularly towards LDCs). Finally, it will investigate the status and the latest developments of organic farming in the LDCs compared to Poland. The research methods used in the article include an analysis of available documentary and literary sources on the topics in question, the development of relevant statistical surveys, and the deductive approach to draw conclusions from the development of organic agriculture in LDCs and Poland (as an example of a Central European Country).